Some remarks on a nonhomogeneous eigenvalue problem related to generalized trigonometric functions. (January 2020) - Cheng, Yan-Hsiou; Wang, Wei-Chuan
Abstract: In this paper, a nonhomogeneous eigenvalue problem with p -Laplacian is studied. We first show the Sturm–Liouville property and derive the asymptotic expansion of eigenvalues and eigenfunctions. Employing the derivation of the eigenfunctions, we discuss the basis property related to the eigenfunctions. Finally, we also solve two inverse problems, the inverse nodal problem and Ambarzumyan problem.